Six new species of Zaischnopsis Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae) from China based on morphological and molecular data - Tang, Hao; Jiang, Jingtao; Wu, Tong; Deng, Jun; Peng, Lingfei (European Journal of Taxonomy, 2022)
Six new species of Zaischnopsis Ashmead (Hymenoptera: Eupelmidae) from China are described, Zaischnopsis covid Jiang & Peng sp. nov., Zaischnopsis fuscolivida Tang & Peng sp. nov., Zaischnopsis lii Jiang & Peng sp. nov., Zaischnopsis pacis Jiang & Peng sp. nov., Zaischnopsis campaniformis Tang & Peng sp. nov., and Zaischnopsis zhongi Jiang & Peng sp. nov. All the new species are described and illustrated based on females, and partial mitochondrial cytochrome oxidase subunit I (COI) sequences are provided for the six new species as well as for the previously described Z. fumosa Peng & Xiang. Females of all the species of Zaischnopsis recorded from China are differentiated in a key.